2016
DOI: 10.1159/000443550
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference in the Role of Posterodorsal Amygdala on the Regulation of Food Intake, Adiposity and Immunological Responses in Albino Wistar Rats

Abstract: Lesion of posterodorsal amygdala (PDA) has been known to produce hyperphagia and obesity in animal models. However, the influence of gender on food intake (FI), body weight (BW) and immunological parameters following PDA lesion is not yet known. The present work was carried out to study the effect of gender on the regulation of FI, BW and immunological parameters following lesions of PDA in albino Wistar rats. Twenty-four albino Wistar rats were divided equally into 2 groups - PDA group and control group - wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Activation of the inferior frontal cortices is associated with top-down control and inhibition processes involved in the self-regulation of food cravings and impulses associated with hedonic ingestion ( 37 ). A negative association between frontal cortical-basal ganglia functional connectivity has been linked to reduced hunger control ( 9 , 10 ), increased weight gain ( 14 ) and appetite ( 6 , 8 ) in obesity. When viewed together, our results may explain why the modulation of impulse control is more associated with increased hedonic ingestion and obesity in women than in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the inferior frontal cortices is associated with top-down control and inhibition processes involved in the self-regulation of food cravings and impulses associated with hedonic ingestion ( 37 ). A negative association between frontal cortical-basal ganglia functional connectivity has been linked to reduced hunger control ( 9 , 10 ), increased weight gain ( 14 ) and appetite ( 6 , 8 ) in obesity. When viewed together, our results may explain why the modulation of impulse control is more associated with increased hedonic ingestion and obesity in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…Although women have an increased propensity to gain total body fat, especially subcutaneous abdominal fat when compared to men, men tend to have more visceral adipose tissue, which has been associated with increased metabolic and cardiovascular disease ( 5 ). Sex differences in eating behaviors have also been identified in both rodent and human experiments ( 6 ). Food cravings, whether cue-induced, trait-related, or state-related, can lead to increased hedonic eating behaviors, which has also been associated with increased risk of obesity ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies in the USA suggest similar rates of obesity in men and women , international studies show a greater prevalence in women . Furthermore, striking sex differences have been observed in eating behaviours and food cravings, resulting in an increased risk for obesity . For example, women with obesity report higher food addiction behaviours, cravings, comorbidity and reward sensitivity than men with obesity .…”
Section: Introductionmentioning
confidence: 99%
“…This may be the reason why the CMA and BLA, but not the SFA, showed significantly abnormal rsFC with the fronto-temporo-insular cortical areas in patients with FD compared with HS in this study. Furthermore, many studies have demonstrated that the BLA and CMA serve as the main amygdala subregions involved in processing food intake and visceral sensation (21,22,38,39). Thus, the altered BLA and CMA rsFC in this study may suggest abnormal visceral sensory input and output connections of the amygdala in FD.…”
Section: Discussionmentioning
confidence: 99%
“…in patients with FD (1319). Among these altered brain regions, the amygdala is believed to be one of the key regions in the central pathogenesis of FD (1517,20) because of its wide involvement in processing interoceptive signals of fullness and satiety (21), food intake (22), endogenous pain inhibition (23), and emotion expression and regulation (24,25). In addition, the role of the amygdala in sex-related difference in cerebral activity has also been identified in brain imaging studies performed on healthy subjects (HS) (23,32,33), patients with irritable bowel syndrome (IBS) (30,31), and patients with chronic visceral pain (23).…”
Section: Introductionmentioning
confidence: 99%